Interleukin-20 is triggered by TLR ligands and associates with disease activity in patients with rheumatoid arthritis - Šenolt, Ladislav; Prajzlerová, Klára; Hulejová, Hana; Šumová, Barbora; Filková, Mária; Veigl, David; Pavelka, Karel; Vencovský, Jiří (Cytokine, 2017)
BACKGROUND: Interleukin (IL)-20 is a pro-inflammatory cytokine that may be implicated in the pathogenesis of rheumatoid arthritis (RA). This study aimed to determine the association between IL-20 and disease activity in patients with RA. METHODS: The levels of serum and synovial fluid IL-20 were measured in patients with RA and OA. The disease activity was assessed based on the Disease Activity Score of 28 joints (DAS28). The expression of IL-20 in synovial tissue samples from patients with RA and OA were determined by immunohistochemistry. Immunofluorescence staining was used to co-localize IL-20 with selected cells. The secretion of IL-20 was analysed in human peripheral blood mononuclear cells (PBMCs) of patients with RA. RESULTS: Synovial fluid and synovial tissue IL-20 were significantly increased in patients with RA compared with patients with OA. The expression of IL-20 in RA synovial tissue was particularly associated with macrophages and neutrophil granulocytes, but also with synovial fibroblasts and lymphocytes. The IL-20 levels in synovial fluid correlated with DAS28 (r=0.434; p=0.015) and were significantly elevated in anti-CCP positive RA compared with anti-CCP negative RA (122.3±104.1pg/ml and 45.9±35.8pg/ml; p=0.008). IL-20 production from PBMCs was induced by Poly I:C and LPS but not with pro-inflammatory cytokines, such as TNF-α or IL-1. CONCLUSION: Our data showed that IL-20 is independently associated with RA disease activity and may be triggered by TLR ligands at local sites of inflammation.
Keywords: Interleukin-20; dospělí; zánět; Arthritis, Rheumatoid; Female; Rheumatoid arthritis; lipopolysacharidy; revmatoidní artritida; Adult; ženské pohlaví; Immunohistochemistry; Leukocytes, Mononuclear; lidé; interleukiny; synoviální tekutina; Disease activity; Lipopolysaccharides; imunohistochemie; Ligands; Inflammation; Male; Aged; Synovial Fluid; lidé středního věku; Interleukins; Toll-Like Receptors; senioři; mužské pohlaví; toll-like receptory; Middle Aged; leukocyty mononukleární; ligandy; Humans